A Stage of Her Own? 'Michele Lu Lanzone' as Blueprint for Franca Rame's Emancipation. (2nd January 2020) - Angelucci, Malcolm; Kolsky, Stephen
ABSTRACT: This article addresses L'operaio conosce 300 parole, il padrone 1000, per questo lui è il padrone (1969), one of the first plays produced by the couple Dario Fo and Franca Rame after their rupture with the mainstream bourgeois theatrical circuit. Through a close reading of one section of the play – the monologue 'Michele lu Lanzone' – we trace the beginnings of a process of re-negotiation of Rame's role within their professional relationship. We argue that the monologue both represents and plays out a series of tensions around ideological, artistic and gender issues, thus 'othering' the female protagonist from the rest of the piece and its didactic message. We also show how the complex intersections of discourses and agendas that constitute the tension within L'operaio are in fact the ongoing context in which Rame will 'find her own voice', gaining independence without ever abandoning the partnership.